A Bionic Hand Pineapple Picking Rod - Yanlong Zhang,; Xi Chen,; Zhanyu Zhu,; Zhaoxi Yang,; Qi Bai,; Ruimin Zhao, (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
Pineapples are only hand-picked hardly, time-consuming and strenuous apparently, for the special picking way. Pineapple harvesting cost accounts for a high proportion of the entire process, which leads to inefficiency and low profit. This project designs a low-cost picking tool that can protect pineapple farmers. The mechanical structure proposed is a combination of a pull rope and a planar four-bar mechanism. When the rope is pulled, the gears small and large are driven accordingly, which can enlarge bite force of cutter working through angle reducing user's pressure. In addition, it equipped with export pipelines and trucks, which solves the difficulty farmers has to carry heavy fruit baskets in low-growing and dense bushes. It greatly improves pineapple picking efficiency and is of great significance alleviating the farmer labour intensity, which promotes development of the pineapple picking industry.